EDUPRENEURSHIP-BASED COMMUNITY EMPOWERMENT THROUGH CUCUMBER FOOD CREATIONS - Billy Hari Pamungkas; Muhammad Faisal Najmudin; Nafiza Izzarulloh; Purnomo Purnomo (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2022)
This study discusses "Edupreneurship-based Community Empowerment through Cucumber Food Creations" conducted by researchers in Cirawamekar Village, Cipatat District, West Bandung Regency. This study aims to explain how edupreneurship-based community empowerment is carried out by a student team from the Pendidikan Masyarakat UPI Laboratory through a Holistic Village Development and Empowerment Program grant (PHP2D) funded by the Ministry of Education and Culture of the Republic of Indonesia. This study uses qualitative methods, data collected by interview, observation and documentation. The results of the study show that community empowerment programs can run well if community participation is built, so that it has an impact on people's skills and income. The environment is an asset that can be utilized, so that it will create local wisdom products that have a selling value. Cucumber chips processed food product, as a creative product of an empowerment program that can be an alternative income if the price of cucumber drops.